(untitled) (Scientific journal of the Fergana State University, 2025)
This article covers the organic matter in the soil in agriculture, the role of microorganisms in them, their activities, microbiological processes in the soil, nitrogen-fixing microorganisms found in the soil and their methods of study, the study of soil fertility using selective culture of Clostridium pasteurianum bacteria from free-living nitrogen-fixing microorganisms.